Pengaruh Kemampuandan Keterlibatan Pengguna Pada Efektifitas SIA Dengan Budaya Organisasi Sebagai Pemoderasi - Astika Putra, Putu Pande Ryan Ananta; Asri Dwija Putri, I Gst. Ayu Made (E-Jurnal Akuntansi; Vol 26 No 1 (2019)DO - 10.24843/EJA.2019.v26.i01.p11, 2019)
The purpose of this study was to determine the effect of user ability and user involvement on the effectiveness of SIA use in SPPBE companies in Bali, and to determine the influence of organizational culture in moderating the ability and involvement of users in SIA in the company. The population in this study were employees of SIA users in all SPPBE companies in Bali. The sampling method is non-probability sampling with saturated sampling technique, so the number of samples is 165 people. The analysis technique used is using the Moderated Regression Analysis technique. Based on the results of the study indicate that the ability and involvement of users have a positive and significant influence and organizational culture is able to moderate the influence of ability and user involvement on the effectiveness of the use of SIA. Keywords: user ability, user involvement, effectiveness of SIA, organizational culture